Hierarchical structural driven model for integrative information management architecture - Mohd Tamrin, Mohd Izzuddin; Tengku Sembok, Tengku Mohd; Kartiwi, Mira (Helvetic Editions LTD, Switzerland, 2013)
Heavy reliance on the other nodes in a complex supply chain network and failure to deliver the specialized assignment by merely one node can caused disruption to the entire processes. The authors introduce the Integrative Information Management Architecture (IIMA) to generate semi-automated assistance against common supply chain deviations. Support models are used and they are made from tree-like structure in XML documents. The recommendations are stored in the leaf nodes whereas the intermediary nodes are filled with characteristics of the deviation. The IIMA employed the XPath together with a series of questions to navigate through the relevant path. We had developed the prototype of the IIMA but run it in simulated environments. The results showed that the group with IIMA support improved the number of completed processes compared to without the IIMA support.